BUCKWHEAT LEAF-AREA DURATION IN TERMS OF SPRING AND SUMMER SOWING IN WESTERN FOREST STEPPE - Осадчук, О. О.; Гаврилянчик, Р. Ю. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article is concerned with the research results on assimilative surface forming of buckwheat crop according to terms of sowing, foliar fertilizing and application at certain phases of plant growth and development in the Western Forest Steppe. The results of the study indicate that the best time for period for buckwheat sowing according to the indicator of leaf-area duration is spring. This indicator varied from 264.2 cm² to 282.0 cm² on the basis of one plant and from 39.9 to 45.4 thousand m² per ha on the basis of sowing. The study has confirmed that leaf-area duration increased at 13.2 with the help of Vuksal Bio Aminoplant application at the mentioned period of sowing during bud stage. The lowest indicator of assimilating surface was fixed in terms of after-harvest sowing period. It varied from 191.7 cm² to 199.2 cm² on the basis of one plant and from 29.0 to 31.4 thousand m² per ha on the basis of sowing. It has been found that the leaf-area duration increased only at 7.9% on the basis of sowing using Vuksal Bio Aminoplant at the mentioned period of sowing during bud stage. The obtained results make it possible to conclude that term of sowing, foliar fertilizing and application at certain phases of plant growth and development influence on assimilating surface forming and indicators of buckwheat performance